Relationship among electrical conductivity, pH of soaked-water, seed germination and seedling growth of corn (Zea mays L.) under two experimental conditions (Scientia Agropecuaria, 2011)
Corn (Zea mayz L.) seeds of twelve lots of different acquisition years were used to study the relation among the measurements of electrical conductivity (EC) and pH of the soaking water and the germination in laboratory, under normal conditions (NC) and accelerated aging (AA) of seeds. A randomized complete block design was used with four replications, an analysis of variance was applied and differences among seed lots were detected by Least Significant Difference Test. Seed lots showed high percentage of germination at eight days of evaluation in (NC) and the unfavorable effect of AA was demonstrated. Dry shoot and radicle weights showed significant differences among the lots. Values of EC were related to percentage of germination in laboratory under AA. Seed lots that showed high percentage of germination in laboratory, previous AA, presented low values of electrical conductivity, therefore, this test could be good indicative of the behavior of corn seeds under extreme or unfavorable conditions of germination. The test of pH did not show direct relation with the seed emergency in laboratory.
Keywords: Seed quality; stress vigor tests; seedling growth.